Cash flow forecasting - Fight, Andrew
In this book, Pascal Costantini gives a lively and wonderfully readable account of ten years of efforts by a small group of investment analysts to find a reliable, practical and implementable method for valuing and selecting shares. The result of their effort is an original investment methodology called CROCI (Cash Return on Capital Invested), best described as a variation of the economic profit model. For over a decade now, Costantinis group at Deutsche Bank has been using this valuation tool every time it has had to take a view on the pricing of an equity asset, be it a market, a sector or an individual sharein other words, every single working day, since it is this groups job to advise institutional investors on equity valuation. Costantini describes in detail, accompanied by concrete examples in the form of charts and graphs, the precise investment results of the actual implementation of the CROCI approach in the global equity markets since 1996.-